Nanosuspension technology and its applications in drug delivery - Arunkumar, N; Deecaraman, M; Rani, C (Asian Journal of Pharmaceutics (AJP), 2014)
Solubility is an essential factor for drug effectiveness, independent of the route of administration. Poorly soluble drugs are often a challenging task for formulators in the industry. Conventional approaches for enhancement of solubility have limited applicability, especially when the drugs are poorly soluble simultaneously in aqueous and in non-aqueous media. Nanosuspension technology can be used to improve the stability as well as the bioavailability of poorly soluble drugs. Nanosuspensions are biphasic systems consisting of pure drug particles dispersed in an aqueous vehicle, stabilized by surfactants. These are simple to prepare and are more advantageous than other approaches. Techniques such as wet milling, high-pressure homogenization, emulsification–solvent evaporation and super critical fluid have been used in the preparation of nanosuspensions. It has the advantage of delivery by various routes, including oral, parenteral, pulmonary and ocular routes. The present article reviews the current methods used to prepare nanosuspensions and their application in drug delivery.